Jessica's zoo adventure - Pascal, Francine (Random House Children's Books Toronto, 1991)
Lost And Found !Identical twins Jessica and Elizabeth Wakefield are excited about their class trip to the zoo. They can't wait to see all the animals, especially the monkeys. But when they get there, the monkey house is closed because a young chimp has escaped!Jessica and Elizabeth, along with their friends Todd and Winston, decide to search for the chimp. But soon they, too, are lost! Will they find the chimp, and will the class find them?Don't miss any of the books in this exciting series!